Implementation of Government Analytical Accounting as a need to make transparent the information contained in the General Account of the Republic. (LACCEI, 2024)
The objective of the present investigation is to determine to what extent the Analytical Accounting influences the control of the budgetary management of a Municipality. In previous studies, there are investigations that consider, to a lesser or greater degree, government accounting as a control factor of budget management in government institutions, which has not been widely developed in a municipality. The research was of an application type. The level of research was correlational, the influence relationship between the independent variable (X) versus the dependent variable (Y) was measured and evaluated. The method and design used for this study was correlational. The population of the present investigation includes the 50 most representative officials of the Municipality. The sample is the same as the population, that is, 50 officials, and the variables were evaluated through an applied survey using Spearman's correlation coefficient to determine the type of association, from which an acceptable correlation coefficient was obtained. According to the results obtained, there is a direct and significant relationship between analytical accounting and the budget management of a Municipality evidenced by a correlation coefficient of Spearman's Rho =0.824 that indicates a good significant correlation at the bilateral 0.05 level, with ρ = 0.000 (ρ 0.05), therefore, the main conclusion indicates that Analytical Accounting significantly influences in the Budgetary Management of a Municipality.